Hepatitis B virus X protein activates transcription factor NF-kappa B without a requirement for protein kinase C. - Lucito, R (1992)
The hepatitis B virus X protein stimulates transcription from a variety of promoter elements, including those activated by transcription factor NF-kappa B. A diverse group of extra- and intracellular agents, including growth factors and the human immunodeficiency virus tat protein, have been shown to require a functional protein kinase C (PKC) system to achieve activation of NF-kappa B. In this study we have investigated the molecular mechanism by which X protein activates NF-kappa B. We demonstrate that in hepatocytes, X protein induces a maximal activation of NF-kappa B corresponding to the sequestered pool of factor, which is also activated by phorbol esters. To determine whether X protein requires activation of PKC to stimulate transcription by NF-kappa B, we attempted to prevent transactivation by X protein in the presence of the PKC inhibitors calphostin C and H7. We show that PKC inhibitors do not block X protein activation of NF-kappa B, whereas they largely impair activation by phorbol esters. In addition, activation of PKC is correlated with its translocation from the cytoplasm to the plasma membrane. The subcellular distribution of PKC was investigated by introducing X protein from a replication-defective adenovirus vector, followed by immunochemical detection of PKC in cell fractions. These data also indicate that X protein stimulates transcription by NF-kappa B without the activation and translocation of PKC.